Analysis and intuition effectiveness in moral problems - Julmi, Christian (Journal of business ethics, 2024)
There has been a longstanding controversy in research as to whether moral judgment is the result of an analytical or an intuitive process. Today, researchers increasingly recognize that moral judgments can be the result of both intuition and analysis, and that the two paths can lead to different results. This raises the question as to which of the two processes leads to a better moral judgment. The article develops a typology of moral problems depending on their moral uncertainty and moral equivocality and links the derived types with analysis and intuition effectiveness. The typology considers four types of moral problems: compliance problems (low uncertainty, low equivocality), professional ethics problems (high uncertainty, low equivocality), conformity problems (low uncertainty, high equivocality) and ethical dilemmas (high uncertainty, high equivocality). The article argues that compliance and professional ethics problems are best solved analytically, whereas intuition is assumed to be more suitable for conformity problems and ethical dilemmas. Moreover, the article shows that it is not sufficient to contrast intuition with analysis alone. The higher the moral uncertainty, the more important the interplay of intuition and analysis becomes in making moral judgments.